Comparative investigation on electronic properties of metal-semiconductor structures with variable ZnO thin film thickness for sensor applications - Cicek, Osman; Kurnaz, Sedat; Bekar, Atakan; Ozturk, Ozgur (Elsevier BV, 2019)
Abstract In this work, AuPd/n-GaAs and Ag/n-GaAs metal–semiconductor structures, which is known as Schottky Junction Structures (SJSs), with various ZnO thin film thickness (25–250 nm) classified as Group AuPd and Group Ag were produced to investigate electronic properties on SJSs. The current-voltage (I–V) characteristics of SJSs operating in their forward and reverse regions operating at ±3 V were measured at room temperature (295 K). The electronics parameters such as the series resistance (Rs), the shunt resistance (Rsh), the ideality factor (n) and the barrier height (ΦB0) were calculated by using thermionic emission (TE) theory, Ohm's law, Cheung and Cheung's function and modified Norde's function. Labview® based characterization tool developed to calculate the electronic parameters. The results were compared according to the various thicknesses and different rectifier contacts. Experimentally, if the results are analysed for each group, a (gradual) decrease in ZnO thicknesses is caused by an increase in the values of n, ФB0, RR. In addition, the Rsh values were significantly increased while the Rs values were almost close to each other. As the ΦB0 values, while compatible with the values found in the Cheung and Cheung's function, they are slightly higher than the values found in the TE theory. On the other hand, due to the voltage-dependent barrier height and nature of the used method, ФB0 values from modified Norde's function are a little higher than the TE theory. Finally, it can be clearly seen that electronic parameters of SJSs based on sensor applications can be arranged with various thicknesses according to extracted results.
Keywords: nano-structures; Thin films; Electrical properties; Layered structures; 7. Clean energy